Gastroliths associated with an Aristonectes specimen (Plesiosauria, Elasmosauridae), López de Bertodano Formation (upper Maastrichtian) Seymour Island (Is. Marambio), Antarctic Peninsula - O'gorman, Jose Patricio; Olivero, Eduardo Bernardo; Santillana, Sergio; Everhart, Michael J.; Reguero, Marcelo Alfredo (Cretaceous Research)
The occurrence of a large gastrolith set associated with a specimen referred to Aristonectes sp. is reported here for the first time. The specimen MLP 89-III-3-1 comes from Seymour Island (Is. Marambio), Antarctic Peninsula, López de Bertodano Formation (upper Maastrichtian). The gastrolith cluster is composed of 793 elements (534 in their presumed original state and about 259 that are broken). The gastroliths are described using sedimentological indices. The mean major axis of the gastroliths is 21 mm, the mean Maximum Projection Sphericity is 0.71 and the standard deviation is 0.11. According to Krumbein?s classification, 43.3% are spheroidal (equant), 14.9% are cylindrical (prolate), 34.7% are discoidal and 7.1% are bladed (laminar). Following Powers? roundness categories, 10.1% are very rounded, 29.2% are rounded and 60.7% are subrounded. The mean Maximum Projection Sphericity value indicates a fluvial origin for the gastroliths. Petrographically, the gastroliths comprise rhyolitic volcanites (56.2%), quartz vein material (27.8%), subarkose arenites (14.5%) and laminated, radiolarian-rich mudstones and tuffs (1.5%). The potential geological sources are several formations from the Antarctic Peninsula, such as the Upper Jurassic Antarctic Peninsula Volcanic Group (rhyolitic volcanites), the Permian-Triassic Trinity Peninsula Group (subarkose arenites), and the KimmeridgianeBerriasian Ameghino Formation (radiolarian-rich mudstones and tuffs). All these formations crop out within about 100 km of the locality where the specimen was collected. We also discuss how gastroliths were ingested, concluding that the ingestion was not done individually. Finally, this record of gastroliths provides evidence against the hypothesis of their use for buoyancy control Fil: O'gorman, Jose Patricio. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Cientifico Tecnológico La Plata; Argentina Fil: Olivero, Eduardo Bernardo. ...